The Adventure of English: The Biography of a Language - Melvyn Bragg (Arcade, 2011)
Here is the riveting story of the English language, from its humble beginnings as a regional dialect to its current preeminence as the one global language, spoken by more than two billion people worldwide. In this groundbreaking book, Melvyn Bragg shows how English conquered the world. It is a magnificent adventure, full of jealousy, intrigue, and war—against a hoard of invaders, all armed with their own conquering languages, which bit by bit, the speakers of English absorbed and made their own.